Kinetic-based indexes for the functional evaluation of gait in diplegic children: a preliminary report. Issue 13 (3rd October 2019) - Zago, Matteo; Corsi, Carolina; Condoluci, Claudia; Galli, Manuela
Abstract: We evaluated the feasibility of a set of indexes based on ground reaction forces to discriminate between the degree of severity of spastic diplegia, identified via Gross Motor Function Classification System (GMFCS). A stepwise discriminant ordinal regression analysis performed on a sample of 58 children returned a subset of variables related to the ratio between braking and propulsive vertical forces and anteroposterior timings. Rather, parameters concerning bilateral symmetry were poorly discriminating. The relative simplicity of the selected indexes allows for their easy implementation on existing gait analysis applications for screening purposes.